The Development Of ICTBased Interactive Student Worksheets (LKPD) Assisted By Software Construct 2 For MTS Students - Meyly Andyny (UMSU, 2022)
LKPD (Student Worksheet) is a teaching material used to maximize student understanding. LKPD contains a set of basic student assignments that are equipped with materials, summaries, and implementation instructions in accordance with achievement indicators. The use of LKPD can increase effectiveness and efficiency in the learning process. This study aims to develop ICT-based interactive worksheets assisted by Construct 2 software for class VII MTs students on the subject of the relationship between angles and to determine the eligiblity and student responses to ICT-based interactive worksheets assisted by Construct 2 software for class VII MTs students on the angle pair relationship. The development model used was a 4-D or 4-P model which is modified into three stages, such as the definition stage, the design stage, and the develop stage. The subjects of this study were students of MTs Amaliyah Sunggal class VII using a small scale of 10 students. The research instrument used was a questionnaire consisting of a material expert assessment questionnaire, a media expert assessment questionnaire, and a student response questionnaire. ICT-based interactive worksheets assisted by Construct 2 software on the material of the angle pair relationship that were developed met the criteria for being very eligible to use for grade VII MTs students. The eligibility could be seen from the results of the validator's assessment, where from the results of the material expert's assessment a score of 88.2% was obtained with a very decent category. From media experts, a score of 88.4% was obtained in the very eligible category, and the student response questionnaire obtained a score of 91.8% in the category of very interesting.